2019
DOI: 10.2352/issn.2470-1173.2019.5.mwsf-542
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Steganography Embedding Scheme Dedicated to Color Sensors in the JPEG Domain

Abstract: Using Natural Steganography (NS), a cover raw image acquired at sensitivity ISO 1 is transformed into a stego image whose statistical distribution is similar to a cover image acquired at sensitivity ISO 2 > ISO 1. This paper proposes such an embedding scheme for color sensors in the JPEG domain, extending thus the prior art proposed for the pixel domain and the JPEG domain for monochrome sensors. We first show that color sensors generate strong intra-block and inter-block dependencies between DCT coefficients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…(4) Sampling on four lattices. In [16], the authors have shown that for this development, the stego signal generated on two non 8-connected blocks is independent and that the dependencies between 8-connected blocks are solely due to demosaicking. Consequently, we can use four lattices Figure 2 to sample the stego signal in the DCT domain.…”
Section: Iso1mentioning
confidence: 94%
See 3 more Smart Citations
“…(4) Sampling on four lattices. In [16], the authors have shown that for this development, the stego signal generated on two non 8-connected blocks is independent and that the dependencies between 8-connected blocks are solely due to demosaicking. Consequently, we can use four lattices Figure 2 to sample the stego signal in the DCT domain.…”
Section: Iso1mentioning
confidence: 94%
“…When these dependencies are not taken into account, the embedding scheme becomes highly detectable at high JPEG Quality Factors (QF). To overcome this problem, the authors of paper [16] modeled these dependencies using the multi-variate Gaussian model with the covariance matrix of the stego signal in the DCT domainΣ estimated from a constant-luminosity RAW image altered by shot-noise. The embedding was then designed to respect the required covariance among stego DCT coefficients.…”
Section: Embedding Algorithm In the Jpeg Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…The hiding rate or embedding rate of a image can be computed as [4], [26], Embeding rate = Number of secret bits Capacity of encoding × 100 Both MDE and F5 methods were tested with Support Vector Machine to detect steganalysis probability, the following comparison are prepared after getting the steganalysis detection result. During the performance testing, the error probability and embedding rate were considered with both QF = 50, and QF = 75.…”
Section: B Analysis Using Embedding Ratementioning
confidence: 99%